The impact of high-standard farmland construction on farmers’ agricultural green production technologies adoption behavior - Chen, Chao; Peng, Ruohan; Wu, Zanzan; Ye, Feng (Frontiers in Sustainable Food Systems, 2025)
High-standard farmland construction (HSFC) is crucial for advancing green agricultural development. Based on 1,350 rice farmers’ research data in Jiangxi Province, this study uses a multivariate ordered probit model and mediation effect model to examine the impact of HSFC on farmers’ agricultural green production technologies (AGPTs) adoption behavior and its influence mechanisms. The results show that: HSFC can substantially enhance the adoption of AGPTs among farmers. The mediation effect analysis results show that the socialized agricultural service and land transfer play a partly mediating role between the HSFC and the adoption behavior of AGPTs by farmers. Heterogeneity analysis shows that farmers with high education, high income and in plain areas are more inclined to embrace AGPTs after participating in HSFC. Therefore, the government needs to promote the active utilization of AGPTs among farmers by enhancing support for HSFC, improving the agricultural socialized service system and regulating the land transfer market.